Preventing Ventilator Associated Pneumonia (VAP) in the Neonatal Intensive Care Unit (NICU) and Pediatric Intensive Care Unit (PICU) - Septa Permana; Sri Hendrawati; Herdiman Permana; Aam Amaliah; Agus Hendra (HealthCare Nursing Journal, 2025)
Ventilator-associated Pneumonia (VAP) is a lung infection that occurs in patients who use mechanical ventilation for breathing. Neonates and children with respiratory distress who require mechanical ventilation have a higher risk of developing VAP. Neonates and children using breathing apparatus in the Neonatal Intensive Care Unit (NICU) and Pediatric Intensive Care Unit (PICU) are prone to Ventilator Associated Pneumonia (VAP). Therefore, VAP prevention should be considered one of the most important issues in NICU and PICU care. This study aims to identify VAP prevention efforts in the NICU and PICU. The research design used in this study was descriptive qualitative. This study's sampling technique used the Focus Group Discussion (FGD) with six nurse participants who worked in the NICU and PICU of a regional public hospital in Bandung using a semi structured interview format. Data were analyzed using thematic analysis. Three main themes describe implementing VAP prevention efforts in the NICU and PICU. The first theme concerns VAP prevention efforts that are still not optimal. Some VAP prevention measures implemented include hand washing, gloves usage, sterile suctioning techniques, head up 30-45 degrees, and oral hygiene. At the same time, other actions have not been routinely carried out. The second theme is the existence of barriers to implementing VAP prevention, and the third theme is related to the need to increase the capacity of nurses and support facilities. Based on the study's results, nurses revealed that the implementation of the VAP prevention program in the NICU and PICU had not run optimally, one of which could be caused by limited infrastructure and nurses' competence. Thus, it is necessary to increase the knowledge and skills of nurses related to VAP and provide adequate infrastructure.